1984
DOI: 10.1104/pp.76.3.769
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of 15NO3 Taken Up by Plants in the Light and in the Dark

Abstract: An experiment was conducted to determine the extent that NO3-taken up in the dark was assimilated and utilized differently by plants than NO3-taken up in the light. Vegetative, nonnodulated soybean plants (Glycine max L. Merrill, 'Ransom') were exposed to '5NO3-throughout light (9 hours) or dark (15 hours) phases of the photoperiod and then returned to solutions containing '4NO3-, with plants sampled subsequently at each light/dark transition over 3 days. The rates of '5N03-absorption were nearly equal in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Two specific effects were apparent: (a) total uptake was 38% less in the dark (236 versus 380 Mmol plant-'), and (b) a smaller percentage of the NO3-taken up in darkness was reduced (30% versus 75%). As was noted in a previous experiment (28), most of the '5NO3-present in the plant at the end of the dark period (83%) was located in the root system.…”
Section: Resultssupporting
confidence: 79%
“…Two specific effects were apparent: (a) total uptake was 38% less in the dark (236 versus 380 Mmol plant-'), and (b) a smaller percentage of the NO3-taken up in darkness was reduced (30% versus 75%). As was noted in a previous experiment (28), most of the '5NO3-present in the plant at the end of the dark period (83%) was located in the root system.…”
Section: Resultssupporting
confidence: 79%
“…The results (not shown) were similar to those shown in Figure 4 and inhibitory concentrations of KNO3 stimulated proton influx before causing the ApH to collapse. It has been reported that NO3-is stored in the vacuoles of barley roots during the night and released to the shoots during the day (29). Release of NO3-from the vacuole by a regulated symport is an attractive hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of NO3 on the tonoplast ATPase in vivo also needs to be elucidated. The physiological significance of the N03 -inhibition is unclear and puzzling, because the vacuole stores nitrate (23,29). Nitrate inhibits the mitochondrial F,F0-ATPase and the tonoplast H+-ATPase with a Ki of only 5 to 10 mm (27,31) although it was estimated that the cytoplasmic concentration of nitrate was approximately 4 mM and the vacuolar concentration was greater than 40 mm for barley leaf protoplasts (23).…”
mentioning
confidence: 99%
“…Ion movement across the cell membrane is highly sensitive to changes in soil or root temperature (Chapin, 1974 ;BassiriRad et al, 1993), oxygen concentration of the rooting medium (Epstein, 1972), metabolic inhibitors , and light and\or carbohydrate availability (Rufty et al, 1984 ;Glass, 1989 ;Raper et al, 1991), which strongly suggest the presence of an energy-dependent uptake system. Despite the early recognition by Van den Honert (see Glass, 1989) that root ion uptake is an active process, a clear mechanism of uptake was not put forward until Epstein & Hagen (1952) introduced the concept of membrane-bound transporters or carriers.…”
Section: Root Uptake Kinetics : the Transporter Concept And Definitionsmentioning
confidence: 99%